Evaluation of Fraud Prevention Policies in the National Health Insurance System in Indonesia: Narrative Literature Review - Putri Galuh Inggi; Anhari Achadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Fraud in the National Health Insurance System (JKN) in Indonesia is a serious issue that harms health services and financing. Fraud practices such as phantom billing and diagnosis manipulation threaten the goals of the National Health Insurance (JKN) to provide fair and quality health access. The latest data shows significant losses due to fraud, with a report by the Corruption Eradication Commission revealing the discovery of fraud amounting to IDR 35 billion in three hospitals. To address this issue, the Minister of Health Regulation Number 16 of 2019 is expected to enhance the management and accountability of the JKN Fund, while also encouraging more effective policy evaluation. Objective: This research aims to evaluate the effectiveness of fraud prevention policies in the National Health Insurance System in Indonesia. Method: This research employs a narrative literature review approach, starting with the inclusion of the keywords "Fraud Prevention" AND “National Health Insurance” AND “Method Fraud” AND "Health Care" in several data-based search engines, such as PubMed/Medline, ScienceDirect, Google Scholar, and Garuda. The inclusion criteria for this study are research conducted in Indonesia and published from January 2020 to August 2024, focusing on the evaluation of fraud prevention policies in JKN, resulting in a total of 17 studies. Result: A review of 17 articles indicates a research gap in the fraud prevention policies of the JKN Program, including a lack of empirical studies measuring the impact of these policies on reducing fraud. In addition, research on the experiences and perceptions of stakeholders, particularly healthcare workers and patients, is still limited, as well as the lack of longitudinal analysis to monitor changes in fraud practices. The aspects of information technology and data management systems in fraud prevention have also not been adequately explored, even though they can significantly contribute to the detection and prevention of fraud. Conclusion: Although the policies to prevent fraud in the JKN system have been implemented, their effectiveness remains low due to a lack of coordination among stakeholders, unclear definitions, and weak oversight. Fraud negatively impacts finances and service quality, while the research gap adds complexity to the issue. Therefore, a holistic approach is needed that includes better collaboration, strengthening regulations, and utilizing information technology to enhance the effectiveness of policies.